Digital dermatitis treponemes associated with a severe foot disease in dairy goats. (14th March 2015) - Sullivan, L. E.; Evans, N. J.; Clegg, S. R.; Carter, S. D.; Horsfield, J. E.; Grove‐ White, D.; Duncan, J. S.
Abstract : A UK dairy goat herd was assessed after reports of a severe lameness problem of unknown aetiology. A lameness prevalence estimate was produced and individual clinical examination of 15 randomly selected lame goats was performed. Fifteen animals had foot lesions closely resembling contagious ovine digital dermatitis (CODD) in sheep. Eight of the goats examined presented with typical CODD lesions and seven showed what appeared to be a more severe CODD with under‐running of the sole. Ten biopsy samples were obtained from the foot lesions and tested by PCR for the three previously isolated digital dermatitis (DD) Treponema phylogroups and culture of treponemes was attempted. Ninety per cent of the biopsy samples were positive for Treponema medium/Treponema vincentii ‐like spirochaetes and Treponema phagedenis‐ like DD spirochaetes and 80per cent were positive for Treponema pedis . Spirochaetes were successfully isolated from 50 per cent of lesion samples. Three isolates were identified as belonging to the T. phagedenis ‐like spirochaetes and two were identified as T. pedis . The frequent isolation of similar treponemes to those isolated from bovine digital dermatitis and CODD lesions and the identification of these DD‐associated phylotypes in the vast majority of lesions support the hypothesis that this novel foot condition is associated with infection by DD treponemes, and given the similarities to CODD, it suggests a causal role.